Novelties in the genus Stylosanthes (Leguminosae, Papilionoideae, Dalbergieae) for Mexico - Gama-López, Susana (Phytotaxa, 2026)
Taxonomic and molecular studies support the description of three new species of the genus Stylosanthes (Leguminosae, Papilionoideae, Dalbergieae), occurring in Mexico. These new species are described and illustrated. In addition, habitat data, distribution maps and comparative SEM photographs of the fruits are given for the new taxa and their related species. Stylosanthes leticiana has a wide distribution in Mexico and affinity with S. humilis. Stylosanthes rosalindae is distributed in central-southern Mexico, mainly in the Tehuacán-Cuicatlán Valley, and is morphologically similar to S. subsericea and S. viscosa. Stylosanthes gretheriae grows in western Mexico and has similarities to S. guianensis.